Construction of bounds on the effective shear modulus of isotropic multicomponent materials - Dong, Vu Lam; Chinh, Pham Duc (Vietnam Journal of Mechanics, 2013)
In our previous paper, we constructed bounds on the effective bulk modulus of isotropic multicomponent composites using minimum energy principles and modified Hashin-Shtrikman polarization trial fields. In this paper, following the variational approach, we construct more sophisticated bounds on the effective shear modulus. Applications to particular models are presented.